Impetus of urban horticulture on open spaces: case of Mutare City - Vitalis Basera; Absai Chakaipa; Phamella Dube (Goodwood Publishing, 2020)
Purpose: To understand the impetus of urban horticulture in the Mutare city with explicit motivation on low density areas. Research methodology: The investigation was quantitative in nature, and used a random sample of urban farmers in Mutare city low density areas. The Statistical Package for Social Scientist (SPSS Version 23) was used to analyse data from the questionnaires. Results: The results reveal that Mutare urban agricultural activities are driven by the need for food self-sufficient, income generation and utilisation of urban open spaces. Limitations: The research had limitations on the sample size and also needed to factor in other multiple response questions. Contributions: The findings are useful to urbanites, urban planners, developmental agents and authorities in the development of urban agriculture. Keywords: Urban horticulture, Urban agriculture, Mutare, Impetus, Food security